Design and practice of water allocation rules: lessons from warabandi in Pakistan's Punjab - Bandaragoda, Don Jayatissa (International Irrigation Management Institute, 1998)
Focuses on the existing gap between the traditional design concepts of warabandi - in irrigation water allocation method practiced in Pakistan and Northern India - and its actual practice. Within this focus it also outlines some institutional implications of the present practice of warabandi and identifies further research and policy needs.